PENENTUAN LOKASI MINIMARKET DI KECAMATAN CIBIUK DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Widy Yudha Rahmat Wiyata; Andri Ikhwana (Jurnal Kalibrasi, 2014)
The  economic development and social style, have infact   necesery level physikolog to saved buyer, and good  service ,and quality  products need,  and then the modern market as   necessaries where service does with him self by customer because the market not avallable a service (pramuniaga) , wich special consumer  service ,the modern  market is movement  up in Indonesia is mini market. The same condition in distric not  except  in Garut Regency , wich   the people always do buy  is super market  and mini market , because is easy to  choose  the goods is  need, and save to buy . The aim of riset is to know for minimarket location fixed which based criteria abd alternatif at Cibiuk Regency in Garut. In location minimarket establish with Analytical Herarkhi Proses (AHP) metod. AHP is ones of model establish suport wich development by Thomas Saary (1993). The resul of riset is that  the Analytical herarkhi process (AHP), can do for  identification  to establesh minimarket location at Cibiuk distric in Garut , with to see the location minimarket which to the research.